2021
DOI: 10.1037/cou0000511
|View full text |Cite
|
Sign up to set email alerts
|

Feeling offended by clients: The experiences of doctoral student therapists.

Abstract: Ten doctoral student therapists (8 White, 5 female) in 1 counseling psychology doctoral program located in the Mid-Atlantic United States were interviewed for approximately 1 hour each about their experiences of feeling offended by a client during an individual psychotherapy session. Interview data were analyzed with consensual qualitative research (CQR). Trainee therapists typically felt offended related to their sociocultural identities (e.g., being a woman, LGBTQϩ, racial-ethnic minority), felt frozen after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…Two instruments were used to collect data in this study, including (a) a demographic questionnaire was used to screen participants for inclusion and to record participants demographic information, and (b) a semistructured interview protocol was developed based on a literature review on discrimination from the perspectives of Asian Americans/Asian internationals (Peng et al, 2022) and microaggressions in a therapeutic context (Ahn et al, 2021; E. Yeo & Torres-Harding, 2021) as well as researchers’ experiences of providing psychotherapy and considerations of clinically cultural exchanges.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Two instruments were used to collect data in this study, including (a) a demographic questionnaire was used to screen participants for inclusion and to record participants demographic information, and (b) a semistructured interview protocol was developed based on a literature review on discrimination from the perspectives of Asian Americans/Asian internationals (Peng et al, 2022) and microaggressions in a therapeutic context (Ahn et al, 2021; E. Yeo & Torres-Harding, 2021) as well as researchers’ experiences of providing psychotherapy and considerations of clinically cultural exchanges.…”
Section: Methodsmentioning
confidence: 99%
“…To the best of our knowledge, we only found one study that examined therapists' experiences of being offended by clients (Ahn et al, 2021). This study and Ahn et al (2021) acknowledged how therapists can experience harm in therapy. Although this study highlighted how these events can impact treatment, future research is needed to identify the impact from the client's perspective.…”
Section: Implication For Research Practice and Advocacymentioning
confidence: 99%
See 2 more Smart Citations
“…Th e American Psychological Association Code of Ethics (2017) more explicitly encourages psychologists to "try to eliminate the eff ect on their work of biases based on [social identity] factors, and they do not knowingly participate in or condone activities of others based on such prejudices" (p. 4). Trainees have reported that they have experienced off ensive statements in direct reference to their own identities and have found it diffi cult to maintain an empathic stance ( Ahn et al, 2020 ).…”
Section: Balancing Client Autonomy and Responsibility To Societymentioning
confidence: 99%